LEARNING THE BASIS OF LIFE ACTIVITY BY THE PROJECT METHOD - WERDINGER, SCOTT; RUDOLF, JENNIFER (Main Issues Of Pedagogy And Psychology, 2015)
The article presents the importance of the project method in teaching the basics of life. It contributes to the future success of students in both practical and educational activities. Electronic surveys were conducted among Minnesota school graduates, students, students, teachers, and parents to determine their understanding of success. Based on the study, the authors came to the conclusion that such skills as the ability to be creative and to receive information were rated significantly higher than academic skills: passing tests, the ability to take notes, etc.